Predictors for the use of traditional Chinese medicine among inpatients with first-time stroke: a population-based study - Wei-Sen Chen; Hung-Chih Hsu; Yi-Wen Chuang; Meng Lee; Kuan-Yu Lu; Yi-Fei Chen; Chien-Min Chen (BMC, 2020)
Abstract Background Stroke is one of the major causes of death and disability. The treatments that are provided to patients during hospitalization after an acute stroke are very important in stabilizing their medical condition and enabling the recovery of their motor functions. However, limited information is available regarding the use of traditional Chinese medicine (TCM) during hospitalization for first-time stroke patients. The researchers aimed to investigate the factors affecting TCM use and to provide clinicians with comprehensive information on TCM use among first-time stroke inpatients in Taiwan. Methods The researchers collected and analyzed data, including patient characteristics, TCM use, and TCM prescription patterns, from the National Health Insurance Research Database in Taiwan for first-time stroke inpatients between 2006 and 2012. Results Among the 89,162 first-time stroke patients, 7455 were TCM users, and 81,707 were TCM nonusers. The predictors for TCM use were as follows: age, 45-64 or < 45 years; men; living in a level 2, 4, or 7 urbanized area; insured amount ≥ 576 USD per month; ischemic stroke; hospitalized for first-time stroke for 8-14 days, 15-28 days, or ≥ 29 days; stroke severity index score 0-9 or 10-19; Charlson-Deyo comorbidity index score 0 or 1-2; hospitalization in a regional or community hospital; receiving rehabilitation; and previous experience with outpatient TCM use. An increase in the number of TCM users was observed from 2006 to 2012. Furthermore, 68.8-79.7% of TCM users used acupuncture only, while 17.8-26.1% used both acupuncture and Chinese herbal medicine. Conclusions An increasing number of first-time stroke patients have been choosing TCM as a complementary treatment during hospitalization. Moreover, TCM use is associated with demographic, clinical, and socioeconomic characteristics. These findings may help clinicians comprehensively understand the trend and the important factors affecting TCM utilization among patients who are hospitalized due to first-time stroke.